THE PREVALENCE OF EDENTATIONS IN YOUNG ADULTS IN IASI - Livia Bobu; Carina Balcoș; Ramona Diana Feier; Dana Bosînceanu; Magda Călina Bârlean (Romanian Society of Oral Rehabilitation, 2018)
The loss of teeth in the young adult population is closely correlated with the oral health status, oral health behaviors and socio-economic level. The aim of the study was to determine the prevalence of edentation among young adults in Iasi, Romania. Materials and methods: The study included a total of 285 students of the Faculty of Dental Medicine, "Grigore T.Popa" University of Medicine and Pharmacy Iași, aged between 22 and 26 years. The EGOHID System was used in order to evaluate the oral health status. The data were analyzed by gender, socio-economic level and oral health behaviors using SPSS 15.0 (p<0,05). Results: Out of the 285 subjects 46,7% had partial edentation. The major reason of tooth loss was dental caries (96,5%) followed by traumatic injures (18,2%) regardless the socio-economic status. The most commonly extracted tooth was the first molar both on the upper and lower jaw. The high prevalence of tooth loss was significantly associated with a high carbohydrates intake frequency. Conclusions. The prevalence of tooth loss demonstrates the need of preventive programs in order to control the dental caries and to provide education for oral health.